Studies of x-ray radiation on the Plasma Focus Facility PF-3 - Krauz, V.I.; Myalton, V.V.; Vinogradov, V.P. (Вопросы атомной науки и техники, 2003)
The investigation of the spectral and amplitude characteristics of the X-ray radiation of the plasma focus facility PF-3 (Wmax= 2.8 MJ) has been done. A diagnostics set for X-ray measurements is described. The total energy radiated from the pinch in the spectral range 0.4 - 1.5 keV at the stored energy up to 1 MJ is ~ 10 kJ. Registration of the X-ray radiation spectral structure in the Ne-discharge within the long wavelength spectrum part (~ 100 - 300 eV) have been first done at PF-3-facility. Conclusion about necessity to take into account this spectral range in the total balance of radiation energy has been done.